“THE SPIRITUAL TURN” - Ahmad Sidqi (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2019)
This article discusses the philosophical dimension of post-modern societies. It examines the champion of rationalities of modern human beings and contends its contemporary limits. It argues that the modern rational philosophies that over-simplify the meaning “being” in metaphysical form has led to the civilizational crisis. In religious dimension, modern human has been sacrificing their inner spiritual dimension of humanity. As a response to this crisis, modernity has initiated the birth of “spiritual turn” that modern human tries to reinvent their spirituality, mainly through Islamic Sufism. This article further examines the significance of Sufi concepts of the 14th century Sufi master Ibn Atha`illah (1259-1310). Examining his Sufi concepts from the lights of post-modern philosophy as panacea for modern diseases, this article found that the concept of spiritual knowledge (ma’rifat) is an essential concept as transcending the limits of rationality and materiality of modern philosophy